Optimization of Additive Concentration in Polymeric Membrane Fabrication (High Polymer Concentration) - Lim, Yi Sin (2015)
As technology become more and more advance, it causes water pollution and newly contaminants found in water resources (Hogan, 2014). Membrane technology is one of the diversity of water treatment technologies have been employed in order to meet the water quality standards and water demand. Membranes are classify into microfiltration, ultrafiltration, nanofiltration, and reverse osmosis. In this study, Polyethersulfone (PES) as polymer, N-methyl-2-pyrrolidinone (NMP) as solvent and Powdered Activated Carbon (PAC) as additive were used to fabricate high performance of membranes. Five types of membrane (0% PES-PAC, 1% PES-PAC, 7% PES-PAC, 9% PES-PAC, and 11% PES-PAC) were tested with pure water flux, salt solution flux, and salt rejection to determine the membrane performance in term of permeation rate. The results showed that 11% PES-PAC has the highest flux which is in range of 6.403× 10-5 – 1.3098× 10-4 m3 /m2 s and 0% PES-PAC has the lowest flux which is 8.300× 10-6 – 1.413× 10-5 m3 /m2 s. Meanwhile, highest salt rejection was obtained by 11% PES-PAC which is in range of 56.67 – 79.62 % and lowest salt rejection was obtained by 1% PES-PAC which is 26.94 – 30.12 %. Scanning Electron Microscopy (SEM) was used to study the morphology of each membranes. It showed that membranes with PAC will enhance marcovoid formation of the membrane and increase the porosity. However, addition of PAC in casting solution will decrease the tensile strength. Generally, the overall performances of membrane improved with the increase of PAC concentrations except tensile strength.